Pengaruh Ukuran, Likuiditas, dan Kinera Keuangan Bank Dengan Financial Technology Sebagai Variabel Moderasi Pada Bank Umum Konvensional di Indonesia - Farom, Sogun Al; Hermuningsih, Sri; Kusumawardhani, Ratih (Universitas Batanghari, 2024)
This study aims to determine the effect of bank size, liquidity, and financial performance with financial technology as a moderation variable (Study on Conventional Commercial Banks in Indonesia 2016-2021). The samples used were financial statement data from Bank BNI, BRI, Mandiri, and BTPN for 2016-2021, so 24 samples of this study were obtained because each bank has 6 financial statements. The sampling technique uses purposive sampling. The tests used in this study are validity, reliability, normality, heterokedasticity, multicollinearity, multiple linear regression analysis, moderating regression analysis, partial tests, simultaneous tests, and determination coefficient tests. The results showed that partially the size variable did not have a significant effect on financial performance, but the liquidity variable had a significant effect on financial performance. In the results of the moderation test, size and liquidity variables have a positive and significant effect on the financial performance of conventional banks which is moderated by financial technology variables.